Clinical-epidemiological characterization of alcoholism. Mantua Popular Council - Urquiola Seoanes, Maidelys; Rodríguez Martínez, Yoan Michel; Díaz Blanco, Sol María; Valdés Paín, LLoy; Alfaro Urquiola, Mireilys (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
Introduction: In our country countless efforts are made for the study and treatment of alcoholic patients.Objective: to characterize clinically-epidemiologically the alcoholism in the population over 16 years of age of the Mantua Popular Council, Juan Bruno Zayas polyclinic of the municipality of Mantua in the year 2022.Method: An observational, descriptive, cross-sectional study was carried out, from the universe of 786 alcoholic patients older than 16 years old, a total of 592 were taken by simple random sampling, constituting the sample.  Theoretical, empirical and descriptive statistical methods were used.Results: a slightly high prevalence of alcoholism was determined, more frequent in males, with early onset of the consumption pattern, with a positive family history for consumption, the presence of other harmful habits such as smoking, family and social dysfunction as well as little information regarding alcohol and the consequences of its consumption, were decisive factors in the possible development of alcoholic disease. Digestive diseases and especially dyspeptic disease in its different variants, resulted the most frequently observed morbid entities.Conclusions: It is concluded that alcoholism appears slightly elevated in the population of the Popular Council of Mantua, a favorable situation to carry out integral, multidisciplinary and intersectorial actions, in order to eradicate this bad habit and prevent future complications in the individual, family and society.